Effect of elexacaftor-tezacaftor-ivacaftor on nasal potential difference and lung function in Phe508del rats - Nicole Reyne; Nicole Reyne; Nicole Reyne; Patricia Cmielewski; Patricia Cmielewski; Patricia Cmielewski; Alexandra McCarron; Alexandra McCarron; Alexandra McCarron; Ronan Smith; Ronan Smith; Ronan Smith; et al. (Frontiers Media S.A., 2024)
Introduction:Phe508del is the most common cystic fibrosis transmembrane conductance regulator (CFTR) gene variant that results in the recessive genetic disorder cystic fibrosis (CF). The recent development of highly effective CFTR modulator therapies has led to significant health improvements in individuals with this mutation. While numerous animal models of CF exist, few have a CFTR mutation that is amenable to the triple combination therapy elexacaftor-tezacaftor-ivacaftor (ETI).Methods: To determine the responsiveness of Phe508del rats to ETI, a baseline nasal potential difference was measured. Subsequently, they received ETI daily for 14 days, after which post-treatment nasal potential difference, lung mechanics (via flexiVent) and lung ventilation (via X-ray Velocimetry) were assessed.Results: Chloride ion transport in nasal airways was restored in Phe508del rats treated with ETI, but neither lung mechanics nor ventilation were significantly altered.Discussion: These findings validate the usefulness of this rat model for future investigations of modulator therapy in CF.